THE EFFECT OF RETURN ON ASSETS, CURRENT RATIO, DEBT TO TOTAL ASSETS RATIO, DEBT TO EQUITY RATIO ON DIVIDEND POLICY - Sari Dewi R Silaban; Mitraya Banjarnahor; Norsalita Aritonang; Jessy Safitri Sitorus; Wenny Anggeresia Ginting (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The purpose of this study was to determine the effect of Return On Asset (ROA), Current Ratio, Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER) on Dividend Policy in Consumer Goods Sector Manufacturing companies in Indonesia Stock Exchange. The research method in this study is quantitative, which uses secondary data because data collection comes from existing records at the company. The population in this study were all consumer goods sector companies on the Indonesia Stock Exchange, totaling 75 companies in 2019-2022. The sampling technique used is purposive sampling. The sample used was 20 companies in 4 years. The data analysis technique used is the classic assumption test and multiple linear analysis with the help of the SPSS 21 application. The results of this study show that Return On Asset (ROA), Current Ratio, Debt To Asset Ratio (DAR), and Debt To Equity Ratio (DER) simultaneously affect Dividend Policy. Partially, Return On Asset and Current Ratio have no significant effect on Dividend Policy, Debt To Asset Ratio (DAR) has a positive and significant effect on Dividend Policy, Debt to Equity Ratio (DER) has a negative and significant effect on Dividend Policy.